Toward a Framework for a Budget Law for Economies in Transition - Allan, Bill. (Washington, D.C. : International Monetary Fund, 1994)
This paper discusses basic principles underlying budget law and reviews key features of budget legislation in several OECD countries as a basis for development of budget legislation in economies in transition to a market environment (EITs). It recommends a broad structure and a number of specific provisions that could be included in budget law for EITs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet